ANALYSIS ON EVALUATION CAPABILITY AND REDUNDANCY OF INDICATORS - Yang, Cuirong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The main problem of index design method is to determine the indicators subjectively and lack of confidence degree to extract the original index information. Regarding to this problem, the two-step filter method of the evaluation index was proposed basing on Variation Coefficient method and General Variance maximization principle. The two-step filter method was applied to statistical hypothesis testing method to filter the preliminary index so as to construct a strongly objective and representative index system. Finally, the two-step filter method was used in national missile defense system to select the combat capability evaluation index. The results demonstrate the feasibility of the method.